MYTH OF HAPPINESS FROM THE CONSUMERISM PERSPECTIVE IN SIMONE DE BEAUVOIR’S LES BELLES IMAGES - Tjahjani, Joesana; Dewantari, Sekar (Paradigma: Jurnal Kajian Budaya, 2025)
France's post-World War II, thirty years of glory, resulted in the growth of purchasing power among the French, which triggered growth in consumerism, notably among the bourgeois— France's upper-middle-class society. People believed in a myth that objects are not solely useful for fulfilling needs but also served as a sign of social status, dignity, andcomfort. They equally believed that if the objects are consumed and the associated social standards fulfilled, they maybecome a way to obtain greater happiness. This article aims to examine the myth that happiness can be attained byconsumption and social standard fulfillment in a French consumer society in the 1960s. To do so, Baudrillard’sconsumerism theory is used, which is juxtaposed with Barthes' theories of structural text analysis, semiotics, and myth.This article, whose scope is limited by the narrative elements of the text, shows that the attachment of the people portrayed in the text with consumer goods and social standards can gradually sink the subjectivity of individuals and even erode the unique and principal characteristic that humans share; humanitarian values, as well as generating greater distance between human and true happiness itself.